Possible role of REG Iα protein in ulcerative colitis and colitic cancer. Issue 10 (24th May 2005) - Sekikawa, A; Fukui, H; Fujii, S; Nanakin, A; Kanda, N; Uenoyama, Y; Sawabu, T; Hisatsune, H; Kusaka, T; Ueno, S; Nakase, H; Seno, H; et al.
Abstract : Background and aims: Although regenerating gene (REG) Iα protein may be involved in the inflammation and carcinogenesis in the gastrointestinal tract, its pathophysiological role in ulcerative colitis (UC) and the resulting colitic cancer remains unclear. We investigated expression of the REG Iα gene and its protein in UC and colitic cancer tissues. We examined whether cytokines are responsible for REG Iα gene expression and whether REG Iα protein has a trophic and/or an antiapoptotic effect on colon cancer cells. Methods: Expression of REG Iα mRNA and its gene product in UC tissues was analysed by real time reverse transcription-polymerase chain reaction and immunohistochemistry, respectively. The effects of cytokines on REG Iα promoter activity were examined in LoVo cells by luciferase reporter assay. The effects of REG Iα protein on growth and H2 O2 induced apoptosis were examined in LoVo cells by MTT and TUNEL assays, respectively. Results: REG Iα protein was strongly expressed in inflamed epithelium and in dysplasias and cancerous lesions in UC tissues. The level of REG Iα mRNA expression in UC tissues correlated significantly with severity of inflammation and disease duration. REG Iα promoter activity was enhanced by stimulation with interferon γ or interleukin 6. REG Iα protein promoted cell growth and conferred resistance to H2 O2 induced apoptosis in LoVo cells. REG Iα protein promoted Akt phosphorylation and enhanced Bcl-xL and Bcl-2 expression in LoVo cells. Conclusions: The REG Iα gene is inducible by cytokines and its gene product may function as a mitogenic and/or an antiapoptotic factor in the UC-colitic cancer sequence.